Effects of microbial fermented liquid (MFL) supplementation on feed intake and nutrient digestibility in early lactating dairy cows - Nampukdee, Rutsamee; Polyorach, Sineenart; Thinowong, Anusorn; Lapmee, Anuwat; Jindatajak, Yaungyote; Vijitrothai, Nahathai; Kongrith, Chunya; Klompanya, Ampon (Journal of Mahanakorn Veterinary Medicine, 2022)
The objectives of this experiment was to study effects of microbial fermented liquid (MFL) supplementation on feed intake and nutrient digestibility in early lactating dairy cows. Twelve, crossbred Holstein Friesian in early lactation, 500±30 kg of body weight, were randomly assigned according to completely randomized design (CRD). Treatments were MFL supplement levels, there were 0, 100, 200 and 300 ml/hd/d. Experimental animals were fed total mixed ration (TMR) with a roughage to concentrate ratio (R:C ratio) was 40:60 which contains 12% CP and 70% TDN, rice straw was a roughage source. The result showed that MFL supplementation did not effects on body weight (kg/d), dry matter intake (DMI) (kg/d and %BW) and nutrient intake (kg/hd/d) while when MFL supplementation at 200 ml/hd/d effect on dry matter intake (DMI) (g/kg BW0.75) apparent digestibility of crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) were linearly increase (P<0.05). Based on this study, a could be concluded can be made that MFL supplementation in early lactating dairy cows could improve feed intake and nutrient digestibility.